Zinc Phthalocyanine Photochemistry by Raman Imaging, Fluorescence Spectroscopy and Femtosecond Spectroscopy in Normal and Cancerous Human Colon Tissues and Single Cells - Beata Brozek-Pluska; Arkadiusz Jarota; Rafal Kania; Halina Abramczyk (Molecules, 2020)
Photodynamic therapy is a clinically approved alternative method for cancer treatment in which a combination of nontoxic drugs known as photosensitizers and oxygen is used. Despite intensive investigations and encouraging results, zinc phthalocyanines (ZnPcs) have not yet been approved as photosensitizers for clinical use. Label-free Raman imaging of nonfixed and unstained normal and cancerous colon human tissues and normal human CCD18-Co and cancerous CaCo-2 cell lines, without and after adding ZnPcS4 photosensitizer, was analyzed. The biochemical composition of normal and cancerous colon tissues and colon cells without and after adding ZnPcS4 at the subcellular level was determined. Analyzing the fluorescence/Raman signals of ZnPcS4, we found that in normal human colon tissue samples, in contrast to cancerous ones, there is a lower affinity to ZnPcS4 phthalocyanine. Moreover, a higher concentration in cancerous tissue was concomitant with a blue shift of the maximum peak position specific for the photosensitizer from 691–695 nm to 689 nm. Simultaneously for both types of samples, the signal was observed in the monomer region, confirming the excellent properties of ZnPcS4 for photo therapy (PDT). For colon cell experiments with a lower concentration of ZnPcS4 photosensitizer, c = 1 × 10−6 M, the phthalocyanine was localized in mitochondria/lipid structures; for a higher concentration, c = 9 × 10−6 M, localization inside the nucleus was predominant. Based on time-resolved experiments, we found that ZnPcS4 in the presence of biological interfaces features longer excited-state lifetime photosensitizers compared to the aqueous solution and bare ZnPcS4 film on CaF2 substrate, which is beneficial for application in PDT.